Diary record survey for outbound tourists (Fukuoka, Japan) - Ab Rahman, Syakir Amir (2020)
The diary record survey is one of the quantitative data collection methods in research process. The record survey was used to collect and record the outbound tourists' expenditure among youth Malaysian to Fukuoka, Japan. The record survey covers several tourism sectors namely, accommodation, food and beverage, transportation, shopping and entertainment.